Microfinance institutions' criteria on small business financing in Cameroon - Serge Messomo Elle (The Journal of Entrepreneurial Finance (JEF), 2019)
This study uses MFIs as a unit of analysis to examine the factors of human, financial and social capital that increase the financing of microenterprises' identification of opportunities and exploitation in Cameroon .To attain this objective, a questionnaire was used to collect data from 207 MFIs and analyzed using descriptive and multiple linear regression models. The results revealed that when it concerns the financing of opportunity identification, only human capital variables of Prior knowledge and Business training increase the financing of microenterprises by MFIs in Cameroon. Regarding the opportunity exploitation on the contrary, accumulated business knowledge, business skills and customer networks positively and significantly boost the financing of microenterprise owners by MFIs in Cameroon.
Keywords: G21; G32; L22; O15; 650; Cameroon; Financing; Human; financial and social capital; Opportunity identification and exploitation; Microfinance; Microenterprises